”In memory of The Snow Queen” – Hans Christian Andersen recalled and retold - Zańko, Aldona (Folia Scandinavica Posnaniensia, 2020)
The main focus of the present paper is the so-called ”intertextual revision”, explored as one of the most recent and innovative strategies employed while reviving the legacy of the Danish fairy-tale classic Hans Christian Andersen. In order to illustrate this practice, I discuss a short story entitled Travels with the Snow Queen (2001), by an American writer Kelly Link, which is a reworking of Andersen's world-famous fairy tale The Snow Queen (1844). Link's take on Andersen's tale represents one of the leading directions within revisionary fairy-tale fiction, inspired by feminism and gender criticism. The analysis is centered around the narrative strategies employed by the author in order to challenge the gender logic incorporated into Andersen's account, as well as the broader fairy-tale tradition it belongs to.